2020
DOI: 10.4012/dmj.2018-280
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of dental crown wear —<i>In vitro</i> study

Abstract: The purpose of the study was to test new method for in vitro evaluation of dental material wear with 3D digitization procedure. Thirty dental crowns, made of polyetheretherketone and veneered with composite material, were subjected to wear test. The crown surface was digitized using coordinate measuring machine before and after the performed wear test. Mesh 3D models were reconstructed and average and maximum depth of lost material and volume loss was calculated (GOM Inspect 2016 software). Mean average depth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…31 On the other hand, it was reported that new tactile probes outperformed 3D scanners in terms of accuracy, which could be advantageous during the dental materials evaluation of wear. 40 Vertical height loss and 2D outcomes for tooth/dental material wear assessment were more clinically relevant since tooth size had no effect. 1,44 However, volumetric measurements were more clinically related and provided more information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…31 On the other hand, it was reported that new tactile probes outperformed 3D scanners in terms of accuracy, which could be advantageous during the dental materials evaluation of wear. 40 Vertical height loss and 2D outcomes for tooth/dental material wear assessment were more clinically relevant since tooth size had no effect. 1,44 However, volumetric measurements were more clinically related and provided more information.…”
Section: Discussionmentioning
confidence: 99%
“…39 Virtual object reconstruction using 3D scanners permits analyzing its dimensions and surface. 40,41 Accuracy is fundamental for any scanner, which involves exactness-deviation of the scanned object from its actual geometry and precision-deviation between repetitive scans. 4,42,43 In this investigation, a highaccuracy 3D scanner (<7 μm) was used to limit the impact of the scanner's inaccuracy on results.…”
Section: Discussionmentioning
confidence: 99%
“…There are very few studies in the literature on the wear behavior of reinforced PEEK material used in the dental field. [35][36][37] Moreover, although there are some studies on existing CAD/CAM composites and ceramics, [38][39][40][41] no data has been presented on whether this polymer can be an alternative in terms of wear resistance. Therefore, in present study, it was objected to compare the wear behavior of various composite-based materials, polymers and glass ceramics after two-body wear test.…”
Section: Introductionmentioning
confidence: 99%
“…A restorative materials should have long‐term stability and appropriate wear properties. There are very few studies in the literature on the wear behavior of reinforced PEEK material used in the dental field 35–37 . Moreover, although there are some studies on existing CAD/CAM composites and ceramics, 38–41 no data has been presented on whether this polymer can be an alternative in terms of wear resistance.…”
Section: Introductionmentioning
confidence: 99%
“…This method requires virtual reconstruction of an object using 3D scanners, which allows for a thorough analysis of its dimensions and 3D inspection software. 16,17 However, inconsistent 3D analysis outcomes may be obtained due to the different protocols used by aligned 3D inspection software.…”
mentioning
confidence: 99%